Customer self-service technology usage and experience in the fast food industry in Malaysia - Samengon, Harnidah (2024)
The rapid advancement of technology has revolutionized the fast-food industry globally, including in Malaysia, with many restaurants adopting self-service technologies (SST) that allow customers to interact with electronic services without direct employee contact. Despite the growing use of SST, their adoption has faced challenges, including critical gaps in customer motivation due to insufficient technological knowledge and unfamiliarity with SST interfaces. There remains to be a gap in understanding customer experiences with SST, which is crucial in implementing technological changes effectively. This study aims to investigate: 1) why customers use SST in the fast-food industry? 2) how the customers play their roles in SST usage in the fast-food restaurant? 3) how the management play its role in customers service experience? and 4) how SST impact customers service experience? A qualitative case study approach involved 18 informants, including fast-food customers, management, and non-management employees, using purposive sampling as a sampling procedure. Data were collected through in-depth, semi-structured interviews, focus group discussions, participant observation and document analysis. To ensure the trustworthiness of the findings, the study employed several measures such as triangulation, member checking, and peer debriefing. Triangulation was achieved by using diverse data sources, while member checking involved participants reviewing the findings to confirm accuracy. Later, thematic analysis was employed to identify key themes that addressed the research questions. The study identified four primary motivations for customer SST usage: 1) cater convenience service, 2) provide alternative ordering methods, 3) offer access to lower prices, and 4) forced usage. From the perspective of Service- Dominant Logic, customers were found to assume various roles in SST usage, including 1) motivated co-creators of value, 2) enforced workers, 3) responsible judges for value co-creator, and 4) technological sweepers. Some roles indicate that customers are often compelled to use SST without alternative options. Management plays a crucial role in influencing customer experiences with SST. The study identified three key management roles: 1) developing restaurant hygiene procedures, 2) infuse technology in restaurant service and, 3) provide guidance for customer. These roles significantly impact how customers interact with SST. The research also explored the impact of SST on customer experiences, revealing two main effects: 1) develop social relationship and, 2) increase technology knowledge and skills of customers. In conclusion, this research has significant practical implications, offering actionable insights for fast-food restaurant management to enhance customer satisfaction by improving the reliability and user-friendliness of SST systems and by providing clear guidelines and support for customers. Additionally, the study contributes to the theoretical understanding of SST usage within the Malaysian fast-food industry, advancing the Service-Dominant Logic framework and setting a methodological standard for future qualitative research. These academic contributions provide a foundation for developing more comprehensive SST adoption and customer experience models, influencing theory and practice in service management and technology adoption research.